Insulin Hexamer‐Caged Gadolinium Ion as MRI Contrast‐o‐phore. Issue 42 (4th July 2018) - Taylor, Steven K.; Tran, Timothy H.; Liu, Michael Z.; Harris, Paul E.; Sun, Yanping; Jambawalikar, Sachin R.; Tong, Liang; Stojanovic, Milan N.
Abstract: High‐relaxivity protein‐complexes of Gd III are being pursued as MRI contrast agents in hope that they can be used at much lower doses that would minimize toxic‐side effects of Gd III release from traditional contrast agents. We construct here a new type of protein‐based MRI contrast agent, a proteinaceous cage based on a stable insulin hexamer in which Gd III is captured inside a water filled cavity. The macromolecular structure and the large number of "free" Gd III coordination sites available for water binding lead to exceptionally high relaxivities per one Gd III ion. The Gd III slowly diffuses out of this cage, but this diffusion can be prevented by addition of ligands that bind to the hexamer. The ligands that trigger structural changes in the hexamer, SCN −, Cl − and phenols, modulate relaxivities through an outside‐in signaling that is allosterically transduced through the protein cage. Contrast‐o‐phores based on protein‐caged metal ions have potential to become clinical contrast agents with environmentally‐sensitive properties. Abstract : Hexameric insulin with a Gd III ion captured in its water filled cavity is a high‐relaxivity agent for magnetic resonance imaging that can change its contrast properties upon sensing ions and small molecules.